Outcome Of Benign Breast Tumor Excision Using Ultrasound-Guided Vacuum Assisted Breast Biopsy: A Literature Review - Wibisana, I Gusti N.G; Kinanthi, Elisabet L.A (UI Scholars Hub, 2024)
Introduction. Benign breast tumors have a significant incidence among breast diseases that cause anxiety for patients. Surgical management is one of the managements. Vacuum-assisted breast biopsy (VABB) could be applied to tumors with a size of less than 3 cm or multiple lesions. One of its techniques is guided by ultrasonography (USG). In Indonesia, the ultrasound-guided (USG-guided) VABB has already been applied in several healthcare instances. Nevertheless, there are still opinions about tumor recurrence after the procedure. This study’s purpose is to observe the tumor recurrence and patients' satisfaction with benign breast tumor excision with USG-guided VABB. Method. Literature was reviewed through the Cochrane Database of Systematic Reviews, PubMed, Scopus, and ProQuest from December 2021 to March 2022. All papers identified were screened and identified. The study's level of evidence and quality were assessed using the Centre for Evidence-Based Medicine, University of Oxford criteria 2011. Results. In total, 1677 studies were found, and after evaluation, 29 studies were relevant—the recurrence rates of benign breast tumors after USG-guided VABB were varied. The lowest being 0% and the highest being 32.6%. Higher recurrence occurs in larger lesion sizes. Moreover, several factors that could be related were lesion size, multiple size, and hematoma in the procedure. Patients' satisfaction was high, including the postoperative scar that is not visible or minimal (5-6 mm). Conclusion. Benign breast tumor management with USG-guided VABB is a good alternative, with a recurrence rate similar to open excision and high patient satisfaction.